Experimental observation of superdiffusive transport in random dimer lattices - U Naether; S Stützer; R A Vicencio; M I Molina; A Tünnermann; S Nolte; T Kottos; D N Christodoulides; A Szameit (New Journal of Physics, 2013)
We experimentally observe anomalous wavepacket evolution in a realization of a one-dimensional finite binary Anderson model in the presence of short-range correlations. To this end, we employ weakly-coupled optical waveguides with propagation constants ε _1 and ε _2 . The correlations enforce the creation of dimers, i.e. two adjacent waveguides with the same ε , randomly placed along the lattice. A transition from a ballistic to a superdiffusive wavepacket expansion and, eventually, to localization is observed as the contrast between the two propagation constants increases.